The identity of Sertularia reptans Linnaeus, 1758 (Bryozoa, Candidae) - Vieira, Leandro M.; Jones, Mary E. Spencer (Zootaxa, 2012)
This paper includes a reassessment of Scrupocellaria reptans (Linnaeus, 1758) (basionym Sertularia reptans), thelectotype of which is selected and figured from among herbarium-sheet specimens held at the Linnean Society of London.Material previously assigned to S. reptans was examined, providing morphological characteristics to distinguishScrupocellaria ellisi n. sp. Scrupocellaria reptans has a geographically limited distribution in the United Kingdom, while S. ellisi is more widespread in the North Sea, Northeast Atlantic, Adriatic and Tasmania.